Contributions to Assessment and Remediation of Acid Tars Lagoons - NICOLAE (TITA), Mihaela; ONUTU, Ion; TITA, Daniel; CHIS, Timur; DOICIN, Bogdan (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Acid tars, a waste unique to the oil processing industry, pose a significant toxicity risk. These by-products originate from refining certain petroleum fractions, such as oil and paraffin, and are commonly found in the waste streams of crude oil processing. In Romania, particularly in the post-war period, acid tars were predominantly managed through storage. Although advancements in catalytic processes have considerably reduced the generation of acid tars in the Romanian refining industry, an efficient treatment method is still required to address the existing acid tars lagoons. The present research refers to a case study carried out on a laboratory scale for the physico-chemical stabilization/encapsulation of acid tars from a lagoon belonging to a refinery in Prahova-Romania county. The experimental program aimed at formulating and applying optimal stabilization recipes for acid tar from the selected lagoon was conducted to reduce the total hydrocarbon and toxic metal content, in compliance with Order No. 95 of 12.02.2005 from Romanian legislation. The leaching data showed that the recipes that stabilize and encapsulate acid tar provide a good immobilization capacity for the five heavy metals (Pb, Cd, Cu, total Cr, Ni) and As, while their releases are dependent on the pH- and varies with the total hydrocarbon content of the treated tar. The laboratory study carried out and presented in this work, as well as the results obtained after performing the leaching test, allow the extrapolation and application of this stabilization - encapsulation procedure on a macro-in situ scale and the remediation of the lagoon where the acid tar was stored.